Secondary craters and ejecta across the solar system: Populations and effects on impact‐crater–based chronologies. (9th March 2018) - Bierhaus, E. B.; McEwen, A. S.; Robbins, S. J.; Singer, K. N.; Dones, L.; Kirchoff, M. R.; Williams, J.‐P.
Abstract: We review the secondary‐crater research over the past decade, and provide new analyses and simulations that are the first to model an accumulation of a combined primary‐plus‐secondary crater population as discrete cratering events. We develop the secondary populations by using scaling laws to generate ejecta fragments, integrating the trajectories of individual ejecta fragments, noting the location and velocity at impact, and using scaling laws to estimate secondary‐crater diameters given the impact conditions. We also explore the relationship between the impactor size–frequency distribution (SFD) and the resulting secondary‐crater SFD. Our results from these analyses indicate that the "secondary effect" varies from surface to surface and that no single conclusion applies across the solar system nor at any given moment in time—rather, there is a spectrum of outcomes both spatially and temporally, dependent upon target parameters and the impacting population. Surface gravity and escape speed define the spatial distribution of secondaries. A shallow‐sloped impactor SFD will cause proportionally more secondaries than a steeper‐sloped SFD. Accounting for the driving factors that define the magnitude and spatial distribution of secondaries is essential to determine the relative population of secondary craters, and their effect on derived surface ages.